If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying m + 10 + -14m = -5 Reorder the terms: 10 + m + -14m = -5 Combine like terms: m + -14m = -13m 10 + -13m = -5 Solving 10 + -13m = -5 Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + -13m = -5 + -10 Combine like terms: 10 + -10 = 0 0 + -13m = -5 + -10 -13m = -5 + -10 Combine like terms: -5 + -10 = -15 -13m = -15 Divide each side by '-13'. m = 1.153846154 Simplifying m = 1.153846154
| (3-3/2y)^2 | | -3x+3(5+13)=3 | | x-3+5x= | | 4k-28k=-49 | | 7x-4/5x=6 | | H/5+3=-6 | | 11(4-6x)+5(13y+1)=9 | | 3x+7-5x= | | 4k-14+3/c=21 | | 5h=2 | | 0=2m-18 | | -0.3f+1.3=4.8 | | -18/y+3 | | (x+16)+(x+22)=231 | | y^2-3y/y+3 | | 5(4x)-1/2x=234 | | 9h+4.5-7h+1.75= | | 6x+3x-3= | | 12+7C=103 | | 21-1y=-87+2y | | 6y-5-2y=-31 | | -2/3n-6=18 | | -7+28m=13(2m-3) | | 2v-54=-1v+21 | | 0.5n+0.3n-0.4n= | | 2x=14+2 | | 12-7y=40 | | 12x+y-x+6y= | | 7x-2x+2-x= | | 6n+10=-44 | | 2/3k=4/3 | | 4x^2+176=0 |